Russian and Soviet film adaptations of literature, 1900-2001 : screening the word - Hutchings, Stephen C.; Vernitski, Anat, 1969- (BASEES/RoutledgeCurzon series on Russian and East European studies, 2005)
Examines the importance of film adaptations of literature in Russian cinema, especially during the Soviet period when the cinema was accorded a vital role in imposing the authority of the communist regime on public consciousness.